Flexible SiC-nanowire membrane reinforced pyrocarbon profiled joints with significantly improved thermal shock resistance. Issue 2 (1st February 2019) - He, Song; Li, Kezhi; Liu, Qian; Gu, Shengyue; Song, Qiang
Abstract: To efficiently enhance the bonding performance of two profiled components of carbon/carbon (C/C) composite, a uniform membrane composed of ultra-long SiC nanowires was synthesized by a simple chemical vapor deposition (CVD) method and then spread on a continuous step-wise shaped C/C surface, acting as the nanoreinforcements. This nano-SiC film was further densified by pyrocarbon, forming the pyrocarbon bonding layer to connect two C/C components. Our strategy can effectively solve the problem of inhomogeneous distribution of nano-reinforcements on a complex-shaped surface in comparison with other loading methods such as in-situ growth and reinforce the bonding layer. The SiC-nanowire membrane (SiC-NM) would convert the bonding layer into isotropic and porous structure thus significantly enhanced the strength of the joint. The shear strength of the joints was substantially increased by 117.8%. After thermal shock cycling experiments between 1000 °C and room temperature (RT) in an Ar atmosphere, a maximum of 29.13 MPa was reached. Moreover, after 45 thermal shock cycles, the final shear strength was still 20.16 MPa, which was higher than the initial value.